O ensino de polígonos de Brahmagupta com o amparo do software Geogebra: um contributo da engenharia didática - Maia, Beatriz Maria Pereira (2021)
The subject of History of Mathematics aims to present the development of Mathematics from the studies of ancient civilizations. For this, teachers are faced with the challenge of transmitting such mathematical concepts so that the class becomes interesting and motivating. In this sense, this research aims to present an educational product that guided the teacher to teach Brahmagupta Polygons in order to open paths for the use of dynamic geometry software that contributes to the building of the student's mathematical thinking, stimulating the reflection and the creation of conjectures with its handling. In order to achieve this objective, Didactic Engineering was adopted as a research methodology in its two initial phases, namely, a preliminary analysis, which carried out a review of the literature and review of three universities in Fortaleza; and the a priori analysis, which were elaborated, from the dialectics of the Theory of Didactic Situations, five didactic sequences that guide the teacher for its use in the classroom. It can be concluded, according to the analysis of the university menus that such concepts are not worked in depth and that approximately 0.13% of academic productions dealing with the Brahmagupta Polygons do not point out methodological paths for their teaching, thus highlighting the importance of material that can collaborate with the initial formation of the Mathematics teacher. The aim of this study is to contribute to future research linked to the promotion of the teaching of historical mathematical concepts.